The Influence of Good Corporate Governance, Corporate Social Responsibility and Firm Size on Firm Value Moderated by Financial Performance (Study on Sri-Kehati Index Companies in 2020 - 2024 - Angelia Irdipani; Ferikawita Magdalena Sembiring (Indonesian Scientific Publication, 2026)
This study aims to analyse the influence of Good Corporate Governance, Corporate Social Responsibility, and firm size on firm value, with financial performance as a moderating variable. The research focuses on 10 companies that are members of the SRI-KEHATI index during the 2020–2024 period. The data used is secondary data obtained from annual reports, sustainability reports, and financial statements published by companies and the Indonesia Stock Exchange. The analysis method used was panel data regression with a moderation approach The results indicate that institutional ownership (KI) does not have a significant direct effect on firm value. In contrast, managerial ownership (KM), corporate social responsibility (CSR), and firm size have significant effects on firm value. Furthermore, the moderation analysis shows that financial performance, proxied by ROA, moderates the relationships between all independent variables (KI, KM, CSR, and firm size) and firm value, resulting in significant effects after moderation. These findings show that the firm's value is more influenced by its characteristics and capacity, as reflected in its size, with optimal financial performance supporting this. This research is expected to contribute to investors, management, and the development of the literature on sustainability-based firm values. This study extends prior research by examining firm value in sustainability-oriented firms listed in the SRI-KEHATI Index, which is important because these firms integrate environmental, social, and governance principles that may influence financial performance differently from conventional firms.